2011
DOI: 10.1037/a0026626
|View full text |Cite
|
Sign up to set email alerts
|

Annual review of Asian American psychology, 2010.

Abstract: This article provides a systematic and critical review of all behavioral science research articles about Asian Americans published in 2010. As the second review of the series, we followed the methodology and format employed in the first annual review of Asian American psychology articles published in 2009 (B. S. K. Kim, Wong, & Maffini, 2010) to facilitate a discussion of trends in contents and methods of published research articles in the field. A search using PsycINFO identified 261 articles that were coded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
104
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(110 citation statements)
references
References 278 publications
(362 reference statements)
6
104
0
Order By: Relevance
“…As was the case with all of the previous reviews (Juan et al, 2012;B. S. K. Kim et al, 2010;Okazaki et al, 2011;Wei et al, 2014;Yeh et al, 2013), two subtopics continued to draw scholarly attention: cancer screening and management (n = 15; e.g., K. E. Kim, Chandrasekar, & Lam, 2014) and substance use (n = 26; e.g., S. S. Kim, Lee, Kiang, Kalman, & Ziedonis, 2014). We used Yeh et al's (2013) and Wei et al's (2014) label of viruses: hepatitis B virus (HBV), human immunodeficiency virus (HIV), and human papillomavirus (HPV) to categorize virus-related articles (n = 7; e.g., Tokes et al, 2014).…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…As was the case with all of the previous reviews (Juan et al, 2012;B. S. K. Kim et al, 2010;Okazaki et al, 2011;Wei et al, 2014;Yeh et al, 2013), two subtopics continued to draw scholarly attention: cancer screening and management (n = 15; e.g., K. E. Kim, Chandrasekar, & Lam, 2014) and substance use (n = 26; e.g., S. S. Kim, Lee, Kiang, Kalman, & Ziedonis, 2014). We used Yeh et al's (2013) and Wei et al's (2014) label of viruses: hepatitis B virus (HBV), human immunodeficiency virus (HIV), and human papillomavirus (HPV) to categorize virus-related articles (n = 7; e.g., Tokes et al, 2014).…”
Section: Resultsmentioning
confidence: 49%
“…As in previous reviews (Juan et al, 2012;B. S. K. Kim et al, 2010;Okazaki et al, 2011;Wei et al, 2014), parenting practices and family relationships continued to be the main focus of studies on families (n = 13). Consistent with B. S. K. Kim et al (2010), we also identified a subtopic on language issues (n = 2).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations